Kierunki reform rachunkowości budżetowej na przykładzie krajów Unii Europejskiej - Borowiec, Leszek (The trends in reforms of budget accountancy based on the examples of European Union countries, 2008)
The article presents core elements of the budget accountancy reform which deals with resignation from cash basis in favour of accrual basis. The examples of budget accountancy reforms in European Union countries will be used to present that reforms increase the effectiveness including the factors that stimulate reformative actions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 39-47